2020
DOI: 10.1007/s11187-020-00358-4
|View full text |Cite
|
Sign up to set email alerts
|

Export promotion programs, export capabilities, and risk management practices of internationalized SMEs

Abstract: The purpose of the study is to analyze the effectiveness of public policies on the international performance of the small and medium-sized enterprises (SMEs). Specifically, we investigate the effect of public export promotion programs (EPPs) on two types of organizational capabilities, i.e. export capabilities which have been already used in previous modelization, and international risk management practices as an original variable intended to better explain the effectiveness of public policies on the SME's int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 108 publications
6
57
0
Order By: Relevance
“…The importance of TPO contributions and activities is being studied by a large number of researchers at many universities around the world: researchers have concluded that government export promotion programs are an important export driver that stimulates and helps exporting companies to increase export sales. Catanzaro and Teyssier have found that promoting high-quality exports has a positive effect on international performance [7]. However, there are also studies which conclude that national government export promotion does not have a significant impact on exports; such a finding, as the researchers note, may stem from an unsuccessful choice of group of respondents.…”
Section: Introductionmentioning
confidence: 92%
“…The importance of TPO contributions and activities is being studied by a large number of researchers at many universities around the world: researchers have concluded that government export promotion programs are an important export driver that stimulates and helps exporting companies to increase export sales. Catanzaro and Teyssier have found that promoting high-quality exports has a positive effect on international performance [7]. However, there are also studies which conclude that national government export promotion does not have a significant impact on exports; such a finding, as the researchers note, may stem from an unsuccessful choice of group of respondents.…”
Section: Introductionmentioning
confidence: 92%
“…Studies on the impact of an export promotion programme run by a French government institution (Catanzaro & Teyssier, 2020) and an Italian government institution (Comi & Resmini, 2020) reported conclusive results. SMEs that engage with government institutions through an export promotion programme tend to have better export performance than non-assisted SMEs.…”
Section: Institutional Networking and Smes' Internationalisationmentioning
confidence: 99%
“…The direct export assistance programme categorized into four groups, namely financial support, informational support, export facilitating support and educational support (Hollensen, 2007;Leonidou et al, 2011). Financial support consists of various tax-related benefits and subsidies, insurance cover to overcome losses and related financial incentives (Catanzaro & Teyssier, 2020;Gencturk, 2010). The institutional information support reveals the requirement of foreign firms, prospect foreign market for export opportunities, foreign government regulations and their credit policies for smooth export related operations (Albaum et al, 2008).…”
Section: Export Assistance Programme and Its Measurementmentioning
confidence: 99%
“…The institutional information support reveals the requirement of foreign firms, prospect foreign market for export opportunities, foreign government regulations and their credit policies for smooth export related operations (Albaum et al, 2008). Facilitating activities are crucial for export-related activities as they include trade offices abroad; the government encouraged trade fairs and exhibitions, and sponsoring of others traderelated operations and missions (Albaum et al, 2008;Catanzaro & Teyssier, 2020). The education and training related component of export assistance programme includes the training programme for export activities and insights of export documentation.…”
Section: Export Assistance Programme and Its Measurementmentioning
confidence: 99%
See 1 more Smart Citation